The Effect of Giving NPK Fertilizer On Growth and Results Plant Purple (Solanum Melongena L.) - Bambang Wicaksono Hariyadi; Sutiono; Nurul Huda; Yeni Ika Pratiwi; Fauziatun Nisak (Faculty of Agriculture, Merdeka University Surabaya, 2020)
The research objective was to determine the effect of NPK compound fertilizer dosage on the growth and yield of purple eggplant (Solanum melongena L). The research was carried out at the Nursery, Agribusiness Sub-Terminal, Food Security and Agriculture Service of Surabaya City, on Jl. Ketintang Madya VII Surabaya, East Java with an altitude of ± 5 m above sea level. Conducted from April to June 2018. his study used a randomized block design (RBD) consisting of six dose treatments with three replications and two sample plants. The NPK compound fertilizer dosage treatment included: D0 = without NPK (Control); D1 = NPK 100 kg / Ha; D2 = NPK dose of 200 kg / ha; D3 = NPK dose of 300 kg / ha; D4 = NPK dosage 400 kg / ha; D5 = NPK dose of 500 kg / ha.The conclusion of the study, namely the NPK dose treatment had a very significant effect on plant height, number of leaves, number of fruits and wet weight per plant of purple eggplant (Solanum melongena L). Treatment with NPK dose of 500 kg / Ha showed the highest growth and yield, although statistically it was not significantly different from the NPK treatment dose of 400 kg / Ha and the NPK treatment dose of 300 kg / Ha (optimum dose).